Cross-sectional study examining whether the extent of first-contact access to primary care differentially benefits those with certain personalities to receive preventive services. Issue 3 (7th March 2016) - Pandhi, Nancy; Schumacher, Jessica R; Thorpe, Carolyn T; Smith, Maureen A
Abstract : Objective: The extent of first-contact access to primary care (ie, easy availability when needed) is associated with receiving recommended preventive services. Whether this access benefits patients at risk of preventive services underutilisation, such as those with certain personality characteristics, is unclear. Setting: Secondary analysis of the 2003–2006 round of the Wisconsin Longitudinal Study. Participants: 6975 respondents who reported a usual provider whose specialty was internal medicine or family medicine. Those reporting not visiting a medical provider in the past 12 months, and those who were uninsured were excluded. Primary outcome measures: Receiving mammography, cholesterol testing and influenza vaccination. Adjusted predicted probabilities (aPP) of receiving these services were analysed stratified by personality characteristics overall, and if significant, then interacted with first-contact access. Results: Lower conscientiousness as compared with higher conscientiousness predicted less of all 3 preventive services; mammography (aPP 80%; 95% CI (77% to 83%) vs aPP 85%; (95% CI 82% to 87%)), cholesterol testing (88%; (85% to 90%) vs 93% (91% to 94%), and influenza vaccination (62%; (59% to 64%) vs 66%; (63% to 68%)). Lower agreeableness as compared with higher agreeableness predicted less mammography (77%; (73% to 81%) vs 84%; (82% to 87%)) and less influenza vaccination (59%; (56% to 62%) vs 65%; (63% to 68%)). Lower extraversion predicted less cholesterol testing (88%; (86% to 91%) vs (92%; (90% to 94%)). Lower openness to experience predicted less influenza vaccination (59%; (56% to 63%) vs (68%; (65% to 70%)). For agreeableness, these differences in receiving preventive services did not persist when first-contact access to primary care was present. Conclusions: Certain personality characteristics predicted receiving less preventive care services. For those with less agreeableness, improved first-contact access to primary care mitigated this effect. If these results are replicated in other studies, primary care offices seeking to improve population health through receiving preventive services should prioritise increasing their first-contact accessibility.